Road Safety of Vulnerable Participants in Traffic – Current State and Directions for Improvement - Arnaudov, Borislav (Research Papers, 2021)
Road safety is primary concern to many cities, seeking to be a better place to live. Safety of vulnerable participants in traffic, specifically pedestrians, cyclists, and bikers is a major issue. These three groups are disproportionately represented in statistics of casualties in urban environment, representing the largest share of fatalities. This mandates road safety and security of these participants in traffic to occupy a significant part of planning for sustainable urban mobility. Within the here presented report are listed the major indicators of road safety and additionally are specified the principles that need to be adhered to in order to make safety an achievable goal within the frame of an urban mobility system.The final part provides an overview of specific good practices and summarizes recommendations regarding the possibility to increase the personal safety efficiency of the vulnerable participants in traffic.
Keywords: Vulnerable participants; Sustainable mobility; Urban transportation system; Safety